From the Mother to the Child: The Intergenerational Transmission of Experiences of Violence in Mother–Child Dyads Exposed to Intimate Partner Violence in Cameroon. Issue 5 (March 2022) - Wadji, Dany Laure; Ketcha Wanda, Germain Jean Magloire; Wicky, Chantal; Morina, Naser; Martin-Soelch, Chantal
Intimate partner violence (IPV) is a widespread social problem with serious consequences for the health of both women and their children. However, little is known about the combined effect of maternal childhood abuse and current exposure to IPV with respect to the psychopathological symptoms of the mother–child dyad. In a Cameroonian cultural setting, where IPV affects more than half of women, we aimed to better understand how mother's childhood abuse and current IPV co-occur to lead to psychopathological symptoms in the mother–child dyad. With the help of a non-governmental organization in Cameroon, we recruited 49 mother–child dyads exposed to IPV, along with 25 mother–child dyads who had not been exposed, and who functioned as a control group. All mothers completed a set of questionnaires, including the Revised Conflict Tactics Scale to assess IPV; the Child Trauma Questionnaire to examine their childhood trauma; the Child Behavior Checklist to assess their children's psychopathological traits; the Hospital Anxiety and Depression Scale; and the Symptom Checklist. We found that physical abuse experienced by mothers during childhood was associated with IPV in adulthood, and specifically sexual abuse, p = .001. In addition, we found that the accumulation of maternal childhood abuse and current IPV was related to anxiety and depression symptoms in mothers, all R 2 ≥ .18, all p s ≤ .015, as well as to externalized symptoms in children, all R 2 ≥ .27, all p s ≤ .017. Our results suggest the intergenerational transmission of experiences of childhood abuse and current IPV, which calls for the development of interventions and care strategies for the mother–child dyad.